1996
DOI: 10.1007/bf01328837
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic synthesis of graphite-like boron nitride

Abstract: It is well-known [1, 2] that lithium compounds have a strong effect on the process of formation of boron nitride by the carbothermal method from highly dispersed charges produced by the dissolution method. It is therefore interesting to examine the effect of these compounds on the formation and ordering of the structure of boron nitride in other methods of preparation.Investigations were carried out into the process of nitriding boron and a mixture of boric acid with soot in the presence of lithium compounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…[ 88 ] www.afm-journal.de www.MaterialsViews.com not included), indicating that it has the standard AA′ stacking. [ 93,94 ] More importantly, the Li and NH 3 helped to in situ unzip the BN nanotubes to nanoribbons. It refl ects that the BN nanoribbon has a wellordered stacking.…”
Section: Controlled Edge and Stacking In Bn Nanoribbonsmentioning
confidence: 99%
“…[ 88 ] www.afm-journal.de www.MaterialsViews.com not included), indicating that it has the standard AA′ stacking. [ 93,94 ] More importantly, the Li and NH 3 helped to in situ unzip the BN nanotubes to nanoribbons. It refl ects that the BN nanoribbon has a wellordered stacking.…”
Section: Controlled Edge and Stacking In Bn Nanoribbonsmentioning
confidence: 99%
“…al. 11,12 found in their study on h-BN formation from boric acid + carbamide mixtures that more C remains present at a given temperature while more h-BN forms when Li 2 CO 3 is added to the reaction mechanism. This result may also be taken as an indication that some h-BN forms without use of C when Li 2 CO 3 is added to the reaction mixture when a lithium borate is expected to form.…”
Section: Reaction Mechanismmentioning
confidence: 97%
“…studied the effect of Li 2 CO 3 addition to h-BN formation by different methods like subjecting B 2 O 3 -C mixtures, boric acid-carbamide mixtures to N 2 (g) or ammonia gas. 11,12 They have found Li 2 CO 3 to favorably affect h-BN formation and h-BN crystallinity and have suggested h-BN to crystallize from the lithium borate melt. A similar mechanism may apply in formation of h-BN from B 2 O 3 + C + CaO mixtures subjected to N 2 gas.…”
Section: Reaction Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…Thomas firstly found that the pure t-BN can be thermally transformed into h-BN at a temperature above 1500°C by a process which proceeded analogously to the carbon graphitization process [12]. Moreover, in the presence of boric oxide [13,14], alkali metal borate or alkaline earth borate [15][16][17][18], the rate of the transformation could be increased obviously, while the transformation temperature could be lower. The raw materials such as B 2 O 3 and borate [19,20] are often used in the chemical synthesis of BN, therefore most of the BN synthesized by these methods are t-BN (low temperature) or h-BN (high temperature) [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%